¿Es Paisajes peruanos un libro de viajes? - Wiesse Rebagliati, Jorge Raúl (Pontificia Universidad Católica del Perú. Instituto Riva Agüero, 2015)
It might seem obvious to state that Paisajes peruanos, one of José de la Riva-Agüero’s threegreat books, should be a travel book, as it is , in effect, the wording of a trip really made. Not whithstandingly, not every trip finishes in the form of a textual genre know as a “travel book”. Using the three dicothomies proposed by Luis Alburquerque for identifying a travel book (“factual” as opposed to “fictional”, “descriptive” as opposed to “narrative”, and “objective” as opposed to “subjective”), this paper proves the generic filiation of Paisajes peruanos. What this paper does not prove is why Riva-Agüero used specifically this particular genre tocristalize his idea of “integral Peruanity”.